2021
DOI: 10.1007/s12011-021-02779-y
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicological Risk Assessment of Cu, Mn, and Zn as Essential Elemental Impurities in Herbal Medicinal Products with Valerian Root (Valeriana officinalis L., radix) Available in Polish Pharmacies

Abstract: The toxicological risk assessment (TRA) of elemental impurities (EI) in especially herbal medicinal products (HMP) is a significant challenge for pharmaceutical industry. In Europe, very popular are traditional HMP with valerian root (Valeriana officinalis L., radix) for relief of mild symptoms of mental stress and to aid sleep. The aim of our unique article is the comprehensive TRA of Cu, Mn, and Zn as EI in HMP with V. officinalis L., radix available in Polish pharmacies. This article is a continuation of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…For this reason, a monitoring nickel content in herbal-based pharmaceuticals available in European Union will be desirable. Moreover, herbal medicinal products should be monitored for the presence of other important and potentially hazardous EIs [16][17][18]. Finally, our results are important and may be significant for other scientist and regulatory affairs working in pharmaceutical industry, especially due to PDE-related topics.…”
Section: Conclusion and Recommendationsmentioning
confidence: 82%
“…For this reason, a monitoring nickel content in herbal-based pharmaceuticals available in European Union will be desirable. Moreover, herbal medicinal products should be monitored for the presence of other important and potentially hazardous EIs [16][17][18]. Finally, our results are important and may be significant for other scientist and regulatory affairs working in pharmaceutical industry, especially due to PDE-related topics.…”
Section: Conclusion and Recommendationsmentioning
confidence: 82%
“…It should be underlined that the monitoring of elemental impurities in herbal medicinal products is an extremely rare topic; hence, it would be valuable to carry out a broader study including other elemental impurities to build upon this data like the studies recently described by our group [21][22][23][24][25].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Studies conducted earlier in different countries revealed that herbal preparations contain heavy metals beyond the World Health Organization's (WHO) maximum permissible limit. The studies included but were not limited to the following lead investigators: Haris and Yang in China [13,14], Jurowski in Poland [15,16], Bas gel in Turkey [17], Saper in the United States of America [18], Garvey [19] etc. This may place drug safety at risk and affect public health negatively.…”
Section: Introductionmentioning
confidence: 99%
“…Unsafe samples follow the trend: Hg > Ni > Zn > Mn > Cd > Cu > Pb > Cr > As. Metals exceeding safety limits in samples in varying degrees were documented in Asian[13,14,17], European[15, 16], and American [18] investigations. Metal ions cause toxicity by interacting with cellular structural proteins, enzymes, and membrane systems…”
mentioning
confidence: 99%